Constructing predictable supramolecular architectures using building blocks derived from versatile and ‘green’ synthetic routes - Sinha, Abhijeet Shekhar (Kansas State University, 2013)
A series of four bifunctional ligands based on β-diketonate moieties bearing methyl, chloro, bromo and iodo substituents and their corresponding Cu(II) complexes were synthesized and crystallographically characterized in order to explore the possibility of using relatively weak halogen…halogen contacts for the directed assembly of predictable architectures in coordination chemistry. The four ligands have characteristic O–H...O intramolecular hydrogen bonds, and the structures of the halogenated ligands contain extended 1-D architectures based on C-O...X halogen bonds, which can be explained on the basis of electrostatic considerations. The corresponding Cu(II) complexes show a constant coordination chemistry for all the ligands, wherein the metal ion sits in a slightly distorted square-planar pocket, without any coordinated or uncoordinated solvent molecules. Furthermore, the absence of halogen-bonds in the coordination complexes is due to the depleted charge on the potential halogen-bond acceptors. As a result, the halogen-bonds are unable to compete with the inherent close packing in the crystal lattice, and thus display a head to head close-packed motif for methyl, chloro, and bromo, substituted Cu(II) complexes. The enhanced polarizability of the iodine atom, produces a more electropositive surface which means that this structure cannot accommodate a linear head-to-head arrangement due to electrostatic repulsion, and thus a unique close-packed structure very different from the three iso-structural complexes is observed for the iodo substituted Cu(II) complex.(1) Oximes offer great opportunities in supramolecular chemistry (hydrogen-bond donors), as well as in coordination chemistry (strong coordinating ligands). Hence, we established a versatile and robust mechanochemical route to aldehyde/ketone–oxime conversions for a broad range of aldehydes(2) and ketones(3) via a simple mortar–pestle grinding method. The relative reactivity of aldehydes vs. ketones under these conditions was also explored, along with an examination of the possible connection between reactivity and electronic substituent effects. The growing interest in the oxime (RR′C═N–OH) functionality, and a lack of the systematic examinations of the structural chemistry of such compounds, prompted us to carry out analysis of intermolecular oxime···oxime interactions, and identify the hydrogen-bond patterns for four major categories of oximes (R′ = −H, −CH3, −NH2, −CN), based on all available structural data in the CSD, complemented by three new relevant crystal structures.(4) It was found that the oximes could be divided into four groups depending on which type of predominant oxime···oxime interactions they present in the solid-state: (i) O–H···N dimers (R22(6)), (ii) O–H···N catemers (C(3)), (iii) O–H···O catemers (C(2)), and (iv) oximes in which the R′ group accepts a hydrogen bond from the oxime moiety catemers (C(6)). In order to explore and establish a hierarchy between hydrogen (HB) and halogen (XB) bonds in supramolecular architectures, we designed and synthesized two ditopic HB/XB donors, and screened them with a series of 20 HB acceptors. IR was used as a preliminary and reliable tool to gather information on the presence/absence of HB/XB in the different cases. We were able to get the solved single-crystal data for three of the 40 reactions. In two out of two cases with symmetric ditopic acceptors, both HB and XB were present leading to 1-D infinite chains, which suggests that in a system of “equal opportunities”, both these interactions can be tolerant of each other. In the only case with asymmetric ditopic acceptor, the HB donor binds to the best acceptor, whereas XB donor binds to the second best acceptor. This selectivity can be rationalized on the basis of electrostatic considerations, where the HB donor was shown to have a higher molecular electrostatic potential than the XB donor. Finally, we designed and synthesized a versatile and dynamic metallomacrocycle based on the 2,2'-bipyridyl backbone capable of controlling the metal-metal distance within the macrocycle cavity. The macrocycle was synthesized by high-dilution method and characterized by several spectroscopic techniques (IR, NMR, Mass, UV-Visible). Also, the macrocycle:Cu(II) stoichiometric ratio was determined by Job’s continuous variation method using UV-Visible spectroscopy, and was found to be 1:2, respectively. (1) Aakeröy, C. B; Sinha, A. S.; Chopade, P. D.; Desper, J. Dalton Trans. 2011, 40, 12160. (2) Aakeröy, C. B.; Sinha, A. S.; Epa, K. N.; Spartz, C. L.; Desper, J. Chem. Commun. 2012, 48, 11289. (3) Aakeröy, C. B.; Sinha, A. S. RSC Adv. 2013, 3, 8168. (4) Aakeröy, C. B.; Sinha, A. S.; Epa, K. N.; Chopade, P. D.; Smith, M. M.; Desper, J. Cryst. Growth Des. 2013, 13, 2687.
Keywords: Chemistry; Supramolecular chemistry; Chemistry (0485)